2015
DOI: 10.1002/celc.201500364
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Evidence of Highly Active Fe Impurity Sites on the Surface of Oxidized Au for the Electrocatalytic Oxidation of Water in Basic Media

Abstract: Addition of Fe to Ni-and Co-based (oxy)hydroxides significantly enhances the activity of these materials for electrochemical oxygen evolution reaction (OER). Here, we show that Fe cations bound to the surface of oxidized Au enhance its OER activity, the OER activity increasing with increasing surface concentration of Fe. Density functional theory analysis of the energetics of the OER revealed that oxygen evolution over Fe cations bound to a hydroxylterminated oxidized Au surface (Fe-Au2O3) occurs at an overpot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 51 publications
9
60
0
Order By: Relevance
“…We note that the observed spectral change is within a potential region where Au electrodes undergo surface oxide formation. 27,28 However, if Au oxidation took place, we would expect the Au 4f spectra to exhibit a new component at ~1 eV higher binding energy; such a spectral change was not detected in our measurements ( Figure S7). The additional oxide species appears at a potential at which, according to the cyclic voltammogram, we do not yet expect oxidation of Ni(OH) 2 to NiOOH.…”
Section: Operation Of the Thin Film Electrochemical Cellmentioning
confidence: 60%
“…We note that the observed spectral change is within a potential region where Au electrodes undergo surface oxide formation. 27,28 However, if Au oxidation took place, we would expect the Au 4f spectra to exhibit a new component at ~1 eV higher binding energy; such a spectral change was not detected in our measurements ( Figure S7). The additional oxide species appears at a potential at which, according to the cyclic voltammogram, we do not yet expect oxidation of Ni(OH) 2 to NiOOH.…”
Section: Operation Of the Thin Film Electrochemical Cellmentioning
confidence: 60%
“…However, it is generally accepted that the OER overpotential decreases dramatically for increase in Fe content from 0 to 10%, reaches a minimum at some concentrations in the range between 10% and 50% and further increases for Fe content higher than 50% (Figure 5b). Interestingly, despite the presence of Fe has a beneficial positive impact on the OER activity, [45,84,92] pure Fe oxyhydroxide electrodes were reported to catalyze the OER with high overpotentials in alkaline conditions. Ni hydroxides have been extensively studied as catalysts for OER and many Ni hydroxide based catalysts have been reported to exhibit superior OER activity in alkaline and near neutral borate buffered electrolyte.…”
Section: Fe Contentmentioning
confidence: 99%
“…[2] In particular, mixedmetal or alloy electrodes are attracting great interest as viable alternatives to the expensive Ru and Ir-based catalysts. [8][9][10][11][12][13][14][15] This fact was not clearly realized before,b ecause the observation of as ignificant improvement of OER activity was hampered by the poor conductivity of the OER-active material containing the Fe 3+ species,typically FeOOH. [6,7] Va rious research groups demonstrated that Fe 3+ plays ak ey role in OER.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] This fact was not clearly realized before,b ecause the observation of as ignificant improvement of OER activity was hampered by the poor conductivity of the OER-active material containing the Fe 3+ species,typically FeOOH. [14,15] However,t hese electrodes are formed upon alkaline oxidation of Au surfaces and subsequent adsorption of Fe 3+ OER active sites,w hich does not allow ap recise control of iron-loading and overall chemical composition. [11][12][13][14][15] Tw o recent papers reported as ignificant improvement of OER activity in alkaline conditions when the surface of gold was doped with Fe 3+ species.…”
mentioning
confidence: 99%
See 1 more Smart Citation